Policy Innovation Net Zero Emission: Partisipasi Masyarakat Jangka Panjang dalam Program Bojonegoro Peduli Emisi Karbon - Roza Assabila Fatimatuz Zahra; Muhammad Miftahul Huda; Rupiarsieh Rupiarsieh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the level of long-term community participation in the Bojonegoro Carbon Emission Care Program by referring to Arnstein's Ladder of Citizen Participation theory (1969). This study uses a qualitative approach with a case study type to explore in depth the form of community involvement in environmental programs that focus on achieving the Net Zero Emission target. Data analysis was conducted using NVivo 12 Pro, which shows that community participation is predominantly at the Tokenism level, namely involvement provided by the government is formal and does not significantly influence the decision-making process. The results of the analysis show variations in the level of community participation, with the highest level of participation shown by Mr. Khafid (25%), followed by Mr. Choiri (24%), Mr. Edi (21%), and Mrs. Damai, Mrs. Suwiji, and Mr. Dedik (19% each). Lower levels of participation were seen in Mrs. Kasiati (18%) and Mr. Soehirman (14%). Tokenism's position is more stable than Non-Participation and Citizen Power, indicating that the community has been involved in various program activities, but does not yet have a strong space to determine policy direction or exert real influence on decisions made. This finding emphasizes the importance of the government's commitment to expanding more substantive participation through outreach, mentoring, and the establishment of inclusive collaborative mechanisms to support the achievement of Net Zero Emissions in Bojonegoro Regency.